Transient Thermal-Electric Analysis of Peltier Cooling Plate for Developing a Mini Refrigerator - Chatchapat Chaiaiad; Jatuporn Thongsri (My University, 2024)
This article reports a transient thermal-electric analysis (TEA), a simulation of a Peltier cooling plate (PCP) aimed to develop into a mini refrigerator soon. This conventional PCP includes 110 Peltier cells, which are a series of connecting cells, and two sandwiched ceramic plates. First, the experiment measured the PCP's applied current (I) and temperature (T) under the desired conditions. Then, the TEA was employed to determine the I and T of the PCP, which were compared with the experimental results. As expected, the comparison shows the consistency between the simulation and experimental results, validating the credibility of the methodology and simulation results. The simulation results revealed that the temperature difference $(\Delta T)$ between the two sandwiched ceramic plates increased with the increase of I and the number of cells, as expected. Last, the proposed model of PCP, I of 500 mA, 126 Peltier cells, and reducing the gap between cells, could generate T of $-2.3761^{\circ}C$ on the cool ceramic plate lower than the conventional model of $-1.6495{ }^{\circ} \mathrm{C}$, about 44% reduction at the same I, suitable for developing the mini refrigerator. The novel of this article is the practical methodology of using transient TEA to help design the PCP for specific purposes.
Keywords: Advanced Thermoelectric Materials and Devices; Refrigeration and Air Conditioning Technologies; Advanced Thermodynamic Systems and Engines